(untitled) (Nordic Journal of African Studies, 2000)
Perhaps the most enduring, even if not the most accurate, image of Africa in the seventies, eighties and nineties has been that of a continent of violence perennially on the edge of survival... Africa thus stands singled out as a continent of uniquely violent politics, a continent where force makes the everyday life of the people even more demeaning than in other poor parts of the world.